PENENTUAN KONDUKTIVITAS LISTRIK DAN KAJIAN KUALITAS AIR SUNGAI SIAK MENGGUNAKAN METODE JEMBATAN WHEATSTONE - Alan Perdana Aritonang; Riad Syech; Walfred Tambunan (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
A research has  been done on  the determination of the electrical conductivity and  water quality  of Siak River water  using a Wheatstone bridge method  in   the  location around the rubber factory   of PT. RICRY. The research was begun by taking samples  of the Siak river water were taken on  five  points  which  have been determined at a distance of 10 meters from PT. RICRY when was low  and high  tide. Based on the  length  data  of wire L1  and L1,  it  could  be determined  the value of electrical resistance, resistivity  and electrical conductivity. The result showed that the value of  highest  electrical conductivity of the river  water  when the  sea  water was  at  high tide  was  58,513  .  10-6 (Ωm)-1, while the electrical conductivity of  the river  water at low tide  was 41,879  . 10-6 (Ωm)-1. A decent water for consumption has an  electrical conductivity of (300  -500).106(Ωm)-1(Mailinda, U. 2011). Based on  that  standard  electrical conductivity, Siak river  water  in  the  research location when the sea water  high tide and low tide are not worthy to be consumed because  of  too small  value  compared  to  the standard   value of electrical conductivity .